Implementasi Modul Antarmuka Perangkat Sensor Dan Komunikasi Pada Uart Dan I2C Dengan Fitur Plug And Play - Bunga Boru Hasian Siahaan; Sabriansyah Rizqika Akbar; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Currently there are many products from various vendors of IOT service providers in the world. The product that intended here is a sensor and Communication Module. Sensor is a device that can sensing a condition and can provide value of the condition. Communication Module is a devices that can allow two or more microcontrollers like Arduino to communicate. Each sensor and Communication Module from each vendor has its own configuration and also its own way to communicating. While users have a variety of needs that sometimes require to combine various devices. Therefore, it takes a way to connect the various sensors and Communication Modules in one module that is a Interface Module, so that it can be easier in its use. In this study there are four sensors and two Communication Modules that connected to one Interface Module. Installation of sensors and Communication Modules with Plug and play features that eliminate configuration during installation. The path used for the installation of sensors is I2C (Inter Integrated Circuit) through path SDA and SCL. Connecting lines with the Communication Module that is UART (Universal Asynchronous Receiver Transmitter) through path RX (receiver) and TX (transmitter). From the test results, the Interface Module successfully detects the Sensor through the address and detects the Communication Module with the translation of the code. Data successfully received from the sensor and successfully forwarded to the Communication Module without configuration.